2014
DOI: 10.9734/ijpss/2014/8412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bradyrhizobium japonicum and Phosphorus Supplementation on the Productivity of Legumes

Abstract: Most soils in sub-Saharan Africa are depleted and lack important nutrients for proper plant growth and development. The declining trend of soil fertility pronounced in different parts of Africa is attributed to different factors such as continuous cropping without soil replenishment and land degradation leading to poor grain yield of legumes. Nitrogen and phosphorus are among the most limiting nutrients for plant growth as they play different roles in the biochemical processes of plants. Phosphorus is a fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…In addition, there was positive correlation of the SPAD index with SNC, which made it possible to use the values of this index as a rapid response in relation to shoot N content. Nyoki and Ndakidemi (2014) also cite the benefits of inoculation with rhizobia and their effect on chlorophyll formation, corroborating the data obtained in this study. Pastorini et al (2016) found no nodules on plants of Machaerium brasilense Vogel without inoculation at 90 days after transplanting to a substrate composed of a mixture of commercial organic substrate and sand (1:2).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there was positive correlation of the SPAD index with SNC, which made it possible to use the values of this index as a rapid response in relation to shoot N content. Nyoki and Ndakidemi (2014) also cite the benefits of inoculation with rhizobia and their effect on chlorophyll formation, corroborating the data obtained in this study. Pastorini et al (2016) found no nodules on plants of Machaerium brasilense Vogel without inoculation at 90 days after transplanting to a substrate composed of a mixture of commercial organic substrate and sand (1:2).…”
Section: Discussionsupporting
confidence: 90%
“…Inoculation with Rhizobia is considered to benefit leguminous crops by increasing nodulation and N 2 fixation, and maximizing yields (Brockwell and Bottomley, 1995). Although the addition of inoculant may increase costs for the producer in the short-term, the long-term benefits in the form of increased yields may outweigh that initial cost (Nyoki and Ndakidemi, 2013). Additionally, re-seeding continued through the end of August in order to maximize the number of plants per species per plot.…”
Section: Year 1 Experimentsmentioning
confidence: 98%
“…According to Chianu et al (2010), in agriculture adverse is taken of the ability to fix nitrogen by legume crops like soybean, cowpea and common beans, all of which generally have the ability to nodulate with a wide variety of rhizomes strains in the soil. According to Nyoki and Ndakidemi (2014) nitrogen fixation is of particular relevance in providing an important source of N, especially in Africa where fertilizers are often not affordable to smallholder farmers and where fertilizer input remains at a very low level. The study was conducted to determine the interaction effect of cropping system, location, season and nitrogen fertilizer on yield and yield components.…”
Section: Introductionmentioning
confidence: 99%